2016
DOI: 10.1080/21645515.2015.1113357
|View full text |Cite
|
Sign up to set email alerts
|

The resurgence of mumps and pertussis

Abstract: Vaccines and extended vaccination programs have had an extensive impact on morbidity and mortality rates due to infectious diseases. Because of the continuous and extensive use of vaccines in industrialized countries, many infectious diseases such as poliomyelitis, diphtheria and measles have been reduced to near-extinction. However, in recent years, many countries including the United States of America, the United Kingdom and Belgium, have been confronted with a resurgence of mumps and pertussis, despite high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…Mumps immunity has also been shown to wane with time after vaccination [31,32]. However, our study found absence of mumps antibodies in all four age groups.…”
Section: Discussioncontrasting
confidence: 55%
“…Mumps immunity has also been shown to wane with time after vaccination [31,32]. However, our study found absence of mumps antibodies in all four age groups.…”
Section: Discussioncontrasting
confidence: 55%
“…The accumulation of susceptible young persons who are brought together in high-density settings can lead to high levels of infection and an increased risk of exposure [27,28]. Mumps outbreaks were recently reported in the US and in Europe, both with high MMR vaccine coverage [27,29]. From 2005 to 2016, 21 mumps outbreaks were reported, and primary school students accounted for 90.21% of the outbreak-related cases.…”
Section: Discussionmentioning
confidence: 99%
“…The cases from Liaoning and Fujian had not received mumps vaccination, the vaccination history of the cases from Shannxi province were unknown, and the cases from Jiangsu province had received one dose of the MuCV but were still infected by MuV. The reinfection of the mumps cases in Jiangsu might indicated that one dose of MuCV could not effectively protect against mumps infection in the susceptible population with the waning of vaccine-induced immune responses; primary immune failure should also be considered [28]. …”
Section: Discussionmentioning
confidence: 99%